2005
DOI: 10.1097/01.phm.0000163703.91647.a7
|View full text |Cite
|
Sign up to set email alerts
|

Soldiers with Occult Traumatic Brain Injury

Abstract: Lew HL, Poole JH, Alvarez S, Moore W: Soldiers with occult traumatic brain injury. Am J Phys Med Rehabil 2005;84:393-398.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 18 publications
0
43
1
Order By: Relevance
“…The following elements are essential to the sequential assessment and treatment of postconcussion symptoms: (1) complete description of altered consciousness and history of functioning from immediately after potential injury events to the present, (2) counseling that targets postconcussion symptoms as early as possible by instilling coping and adaptive strategies, (3) psychotherapy and medical treatments to address any continuing conditions that affect cognitive functions and are potentially reversible (emotional disorders; vision, hearing, and vestibular impairments; orthopedic needs), and (4) comprehensive neuropsychological evaluation to guide further rehabilitation if cognitive difficulties continue despite these interventions or are atypical of known comorbidities. Thus, in serving this initial cohort of PNS patients, we developed invaluable collaborations with numerous professionals in the healthcare system, including the National Center for PTSD, and primary care and mental health clinicians in VA centers throughout the Palo Alto VA's catchment area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The following elements are essential to the sequential assessment and treatment of postconcussion symptoms: (1) complete description of altered consciousness and history of functioning from immediately after potential injury events to the present, (2) counseling that targets postconcussion symptoms as early as possible by instilling coping and adaptive strategies, (3) psychotherapy and medical treatments to address any continuing conditions that affect cognitive functions and are potentially reversible (emotional disorders; vision, hearing, and vestibular impairments; orthopedic needs), and (4) comprehensive neuropsychological evaluation to guide further rehabilitation if cognitive difficulties continue despite these interventions or are atypical of known comorbidities. Thus, in serving this initial cohort of PNS patients, we developed invaluable collaborations with numerous professionals in the healthcare system, including the National Center for PTSD, and primary care and mental health clinicians in VA centers throughout the Palo Alto VA's catchment area.…”
Section: Discussionmentioning
confidence: 99%
“…However, the steady influx of new patients presents a challenge to the system. This challenge arises not only from the increased demand for clinical services but also from returning soldiers' complex combat-related injuries, which were not typically seen in prior wars [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As of May 2010, over 31,800 U.S. servicemembers have been wounded in Operation Iraqi Freedom (OIF) and Operation Enduring Freedom (OEF) [6]. Injuries caused by IEDs are associated with the unusually high prevalence of traumatic brain injury (TBI) [7] and PTSD among the injured [8][9], conditions that are likely to present substantial challenges in reintegrating into community roles. Data suggests that OIF/OEF service will negatively affect a far greater number of persons beyond those counted in the combat casualty statistics, with upwards of 790,000 veterans expected to seek disability benefits for service-related health problems [10].…”
Section: Introductionmentioning
confidence: 99%
“…Now and for the coming decades, larger proportions of veterans will be from racial/ethnic minority groups and more likely to return with an ABI from war-torn countries like Iraq and Afghanistan. However, equally important to recognize is that military personnel in both combat and noncombat posts are at high risk for sustaining an ABI [34][35][36]. One study, for example, found that 23 percent of noncombat, Active Duty soldiers at Fort Bragg (n = 2,276) sustained an ABI during their military service [37].…”
Section: Minority Issues and Veteransmentioning
confidence: 99%